Different biochemical patterns in type II and type III mixed cryoglobulinemia in HCV positive patients. Issue 9 (September 2018) - Basile, Umberto; Gulli, Francesca; Gragnani, Laura; Pocino, Krizia; Napodano, Cecilia; Miele, Luca; Santini, Stefano Angelo; Marino, Mariapaola; Zignego, Anna Linda; Rapaccini, Gian Ludovico
Abstract: Background: Reversible cryoprecipitability of proteins is observed as a concomitant feature of immune complex formation. Mixed cryoglobulinemia (MC) is systemic vasculitis, associated with mixed IgM and IgG cryoglobulins (CGs) showing rheumatoid factor (RF) activity. It is frequently associated with hepatitis C virus (HCV). This study investigates the presence of IgG RF and anti-nuclear antibodies (ANA) in cryoprecipitates of patients with type III and type II MC, to understand the biochemical patterns associated with different types of MC to a greater degree. Methods: Sera from 70 HCV untreated patients with type III or type II MC were tested by immunofixation for IgG3 and through ELISA for IgG RF. Cryoprecipitates were analysed for ANA by indirect immunofluorescence to identify specific patterns. Results: After stratification according to MC type, the ANA patterns between type II and type III MC were statistically different. IgG3 levels and IgG-RF positivity were significantly higher in type III cryoprecipitate. We observed a higher positivity of IgG3 and a significant difference between the liver fibrosis stage, ANA and IgG-RF in the cryoprecipitate. Conclusion: Results show a combination of biochemical markers and autoantibodies associated to mixed cryoglobulinemia; these findings could be further investigated in order to ascertain their usefulness in assessing the risk for the development of mixed cryoglobulinemia.